Aplikasi Value Engineering dengan Metode“Paired Comparison” pada Struktur Pelat Beton - Budi Sutrisno; Mandiyo Priyo (Semesta Teknika, 2013)
This research studied the application of value engineering with a paired comparison method with the case study in Tourism Building of Sleman Regency, Special Region of Yogyakarta. Several steps need to be carried out which consisted of information, creativity, a paired comparison method analysis, development and recommendation for the new design of a concrete plate. The concrete plate was redesigned using 2 alternatives. The first alternative was reducing the thickness of the plate from 12 cm to 10 cm without changing the concrete quality. The second alternative was using precast concrete. The result shows that the first alternative will save project budget to Rp. 10,569,562.-. Moreover, by using precast, the budget for the project will be increased by Rp.4,208,058.-. According to the paired comparison method and alternative comparison evaluation matrix, the second alternative has the highest percentage (59%), while first alternative and current condition only have 25% and 16% respectively. The second alternative was chosen to be applied to replace the existing design since it will gain more profit than any other which were included concrete quality, time, controlling, weather and human resources.